Prenatal homozygosity mapping detects a novel mutation in CHST3 in a fetus with skeletal dysplasia and joint dislocations. Issue 4 (1st March 2017) - Muys, Joke; Blaumeiser, Bettina; Jacquemyn, Yves; Janssens, Katrien
Key Clinical Message: In selected cases, homozygosity mapping followed by direct sequencing of one or a few carefully selected candidate genes in a prenatal setting can be beneficial to obtain diagnosis in consanguineous families. Abstract : In selected cases, homozygosity mapping followed by direct sequencing of one or a few carefully selected candidate genes in a prenatal setting can be beneficial to obtain diagnosis in consanguineous families.